Clinical Impact of the Time in Therapeutic Range on Early Hospital Readmission in Patients with Acute Heart Failure Treated with Oral Anticoagulation in Internal Medicine - Rubén Ángel Martín-Sánchez; Noel Lorenzo-Villalba; Alberto Elpidio Calvo-Elías; Ester Emilia Dubón-Peralta; Cynthia Elisa Chocrón-Benbunan; Carmen María Cano-de Luque; Lidia López-García; María Rivas-Molinero; Cristina Outón-González; Javier Marco-Martínez; Elpidio Calvo-Manuel; Emmanuel Andres; et al. (Medicina, 2021)
Background and objectives: Patients with heart failure (HF) often present with non-valvular atrial fibrillation and require oral anticoagulation with coumarin anticoagulants such as acenocoumarol. The objective of this study was to evaluate the relationship between time in therapeutic range (TTR) and the risk of early readmission. Materials and Methods: A retrospective descriptive study was carried out on hospitalized patients with a diagnosis of HF between 2014 and 2018 who had adverse effects due to oral anticoagulation with acenocoumarol (underdosing, overdosing, or hemorrhage). Clinical, analytical, therapeutic, and prognostic variables were collected. TTR is defined as the duration of time in which the patient’s International Normalized Ratio (INR) values were within a desired range. Early readmission was defined as readmission within 30 days after hospital discharge. Patients were divided into two groups depending on whether or not they had a TTR less than 60% (TTR < 60%) over the 6 months prior to the adverse event. Results: In the cohort of 304 patients, the mean age was 82 years, 59.9% of the patients were female, and 54.6% had a TTR < 60%. Patients with TTR < 60% had a higher HAS-BLED score (4.04 vs. 2.59; p < 0.001) and INR (6 vs. 5.31; p < 0.05) but lower hemoglobin (11.67 vs. 12.22 g/dL; p < 0.05). TTR < 60% was associated with early readmission after multivariate analysis (OR: 2.05 (CI 95%: 1.16–3.61)). They also had a higher percentage of hemorrhagic events and in-hospital mortality but without reaching statistical significance. Conclusions: Patients with HF and adverse events due to acenocoumarol often have poor INR control, which is independently associated with a higher risk of early readmission.